The impact of liquidity, solvency, and company value on the dividend payout ratio: an empirical study in the energy sub-sector in the LQ45 period 2017 -2021 - Hendri, Aqil Azfi (Universitas Wiralodra, 2023)
The capital market is very popular with many people, especially after the Covid-19 pandemic yesterday. The COVID-19 pandemic has made people realize how important it is to save and invest, especially in shares. This research analyzes the influence of liquidity, solvency, and profitability on the dividend payout ratio. The population of this research are companies in the energy department registered in LQ45 for the 2017 - 2021 period using a purposive sampling method with a total of 140 companies. The dependent variables in this research are Cash Ratio, debt-to-debt-equity ratio, and price-to-book value, with the result that the cash ratio affects the dividend payout ratio, the debt-to-debt-equity ratio has an effect on the dividend payout ratio, and price to book value has no impact on the dividend payout ratio.